PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR MENGGUNAKAN ALAT PERAGA GEOMETRI DATAR KELAS III SDN 008 SANGATTA SELATAN - Sunarti, Sunarti (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
This researcher bertutuan to improve the activity and learning outcomes in mathematics through Materials Up Datat Props to the Geometry of the Flat in class III SDN 008 South Sangatta. This research is motivated by low activity mathematics learning outcomes of students class III SDN 008 South Sangatta. Subject this research is students class III SDN 008 South Sangatta which amounted to 20 students. This research type is Classroom Action Research (classroom Action). With research that use is the model Kemmis which includes the stages of planning, implementation of action, observation, and reflection. The instrument of data collection used is the observation sheet. The data analysis technique used is data analysis descriptive qualitative.             Based on the results of data analysis at cycle I of meeting I activity the students showed 30%, meeting 2 shows 39%, meeting 3 showed 47%, the average value of student activity cycle I shows 42%, classified as criteria low. After repair there was an increase in cycle II meeting I Activity the student demonstrates 80%, meeting 2 shows 86%, meeting 3 show that 92%, the average value of students of cycle II showed 86%, quite high criteria. This increase occurs where students always pay attention to his weaknesses and trying to memprbaikinya seemingly on the stages of the cycle that there is always an increase. Increased activity of students can also affect the improvement of student learning which indicates the average percentage of the first cycle 61%, cycle II is 78%. From the results of the research show that props up a flat geometry flat can increase the activity and learning outcomes in mathematics in class III SDN 008 South Sangatta.